Vibration Assessment on Various Distance to Demolition Works - Tuan Chik, Tuan Norhayati; Teck Lung, Eric Soo; Yusoff, Nor Azizi; Tumiran, Mohamad Taufik; Mohd Suhaimi, Ahmad Hafiz Farhan (International Journal of Integrated Engineering, 2020)
Vibration has been a serious problem to be discussed over the past years. Vibration has caused cosmetic damages to buildings and annoyance to the occupants of the building. Sources of vibration are usually produced by construction work, traffic, seismic effect and human activities. In this paper, the amplitude of vibration caused by demolition has been analyzed and the level of vibration and level of damage caused have been determined. Besides, the effect of the vibration strength due to distance from the source has also been studied. The vibration data due to demolition work was obtained and analyzed by using MATLAB software. The analyzed data in graphical form were compared with the Gordon vibration criteria to obtain the vibration limit and the level of vibration damage according to DOE (Malaysia) standard as well. The results indicated that the vibration at 1m distance and 10m distance from the vibration source will cause minor damage to the building whereas the vibration at 25m distance from the source is at the caution level. By comparing the Gordon vibration criteria curve, the vibration from 1m, 10m and 25m distance from the demolition vibration source are not suitable for sensitive equipment. This study also proved that the vibration strength will decrease as the distance from the source increases due to the loss of vibration energy during the propagation of vibration waves. Hence, the further the distance from the source, the weaker the strength of the vibration and lower level of damage on surrounding buildings.